FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN KEBAYA PADA IBU-IBU DAN REMAJA PUTRI - Endang Wani Karyaningsih (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2015)
This research is to know the factors influencing the choice of dress for mothers and daughters in KecamatanGondomanan, covering: 1) the choice of model, 2) the choice of cloth (material), 3) the comfortable of wearing. The questions are what factors influencing the choice of dress and what are the reasons. It is a descriptive research, conducted in KecamatanGondomanan Yogyakarta. The number of population is 100 rspondents, the sampel is 70 respondents taken by incidental technique. To explore the data, the quesionaire is used. The data is analyzed by descriptive analysis. From the research results, it is known that 58,6% select kuthubarudress model, 21,4% select moslem dress, and 20% select modification dress. The reason to thekuthubaru selection is that the dress is polite with simple materials and comfort to wear; those who select moslemdressare cause by the aprropraieness to the Islamic rules and it is alson comfortable; modification models are selected bacuse the model is up to date, it is not old fashion, it has some variation and glamour, and the users feel more self-confidence.